Evaluation of the University of Denver's Center for Separating and Divorcing Families: The First Out‐of‐Court Divorce Option1. (July 2017) - Pruett, Marsha Kline; Cornett, Logan
Abstract : The Resource Center for Separating and Divorcing Families (RCSDF) is the first U.S. alternative dispute resolution model to provide legal dispute resolution, therapeutic, educational, and financial services to separating and divorcing families in a single location outside the courthouse. Data were collected on 82 families at entry and service completion: service utilization, process timeliness, family satisfaction, and outcomes. Parents were highly satisfied with the process and demonstrated significant improvements in personal well‐being, co‐parenting, parenting quality, and reported reductions in children's anxiety/depression. Community partners felt RCSDF was a positive innovation in their community. The RCSDF model represents a culture shift from an adversarial process to a cohesive alternative that supports the well‐being of all family members. Key Points for the Family Court Community: The Resource Center for Separating and Divorcing Families (RCSDF) at the University of Denver was the first interdisciplinary out‐of‐court model, providing a nonadversarial alternative to traditional models of divorce. The model provided comprehensive services from screening and intake through completion, offering legal, mental health, and financial services. In the final step, a retired judge held uncontested permanent order hearings at the Center. Services were provided by teams of law and mental health students, closely supervised by legal and mental health professionals, keeping costs to a minimum for families. Program evaluation with the first 249 families showed that parents with diverse backgrounds participated at the Center out of concerns for their children's adjustment and reorganization of the family and its resources. The average family completed the process in 5–6 months, and parents showed significant improvements in mental health, parenting, and co‐parenting outcomes. Parents and community partners rated their experience with RSDF as a positive experience across multiple indicators. Overall, RCSDF had many successes, leading to a launch of a community‐based model replicating the University‐based Center to maximize sustainability and universal access.